2015
DOI: 10.1016/j.celrep.2015.08.073
|View full text |Cite
|
Sign up to set email alerts
|

Rad53-Mediated Regulation of Rrm3 and Pif1 DNA Helicases Contributes to Prevention of Aberrant Fork Transitions under Replication Stress

Abstract: SummaryReplication stress activates the Mec1ATR and Rad53 kinases. Rad53 phosphorylates nuclear pores to counteract gene gating, thus preventing aberrant transitions at forks approaching transcribed genes. Here, we show that Rrm3 and Pif1, DNA helicases assisting fork progression across pausing sites, are detrimental in rad53 mutants experiencing replication stress. Rrm3 and Pif1 ablations rescue cell lethality, chromosome fragmentation, replisome-fork dissociation, fork reversal, and processing in rad53 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
86
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(93 citation statements)
references
References 68 publications
5
86
0
Order By: Relevance
“…Since this replication defect was independent of the ATPase/helicase activity located in the ordered C-terminal domain of Rrm3 (residues 250–723), we explored a possible involvement of the 230-residue, disordered N-terminal tail (Fig 3A, S4A Fig). The only motifs previously identified in this tail are a putative PCNA-interacting peptide (PIP) box between residues 35–42 [18] and a cluster of phosphorylated residues between S85 and S92 [17]. Deletion or mutation of the PIP-box ( rrm3-ΔN54 , rrm3-FFAA ) had no effect on DNA replication in HU, whereas deletion of the entire N-terminal tail ( rrm3-ΔN230 ) caused the same replication defect as deleting RRM3 ( rrm3Δ ) (Fig 3C).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Since this replication defect was independent of the ATPase/helicase activity located in the ordered C-terminal domain of Rrm3 (residues 250–723), we explored a possible involvement of the 230-residue, disordered N-terminal tail (Fig 3A, S4A Fig). The only motifs previously identified in this tail are a putative PCNA-interacting peptide (PIP) box between residues 35–42 [18] and a cluster of phosphorylated residues between S85 and S92 [17]. Deletion or mutation of the PIP-box ( rrm3-ΔN54 , rrm3-FFAA ) had no effect on DNA replication in HU, whereas deletion of the entire N-terminal tail ( rrm3-ΔN230 ) caused the same replication defect as deleting RRM3 ( rrm3Δ ) (Fig 3C).…”
Section: Resultsmentioning
confidence: 99%
“…A putative PCNA-interaction motif (PIP) between residues 35–42 [18] and a cluster of phosphorylated residues (P) between residues 85–95 [17] are indicated by gray boxes in the disordered tail. N-terminal tail truncations ( rrm3ΔN54 , rrm3ΔN142 , rrm3ΔN186 , rrm3ΔN212 , rrm3ΔN230 ) and point mutations designed to inactivate the PIP box ( rrm3-FFAA) and the Walker A motif of the helicase domain ( rrm3-K260A , rrm3-K260D ) were constructed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Blackburn lab has shown that DSBs, but not stalled replication forks, result in Rad53 mediated phosphorylation of the C-terminus of ScPif1 at T763 and S766 which inhibits telomerase specifically at DSBs [31]. Both ScPif1 and Rrm3 are also phosphorylated in response to replication fork stalling in the N-terminal domain by Rad53 [103]. These phosphorylations inhibit ScPif1 and Rrm3 which prevents fork reversal and genome instability.…”
Section: Regulation Of Pif1 Activitymentioning
confidence: 99%